Design of a safety dashboard for patients. Issue 4 (April 2020) - Gibson, Bryan; Butler, Jorie; Schnock, Kumiko; Bates, David; Classen, David
Highlights: We co-designed a dashboard to engage patients in safety efforts. The framing of the tool's purpose and appropriate use is critical. User-centered design suggests an action oriented interface. Health literacy and numeracy is a fundamental design consideration. Abstract: Background: Nearly one third of hospitalized patients suffer harm from medical errors in U.S. hospitals each year. Objective: Our goal was to design a patient-facing application that is intended to engage patients and their caregivers in reviewing and responding to clinical issues that may have safety implications. Patient involvement: We conducted user-centered design sessions with recently hospitalized individuals and /or informal caregivers. Methods: We conducted five user-centered design sessions with total of 37 individuals. Sessions began with individuals sharing personal stories of recent hospitalizations and any experienced safety events. We then solicited feedback on the current iteration of the patient-facing safety application. The design of the app was updated between sessions. Results: The design of our app centers around three key findings. First, involving patients in safety promotion is novel to most patients and their caregivers: therefore the framing of the tool's purpose and appropriate use is critical to engage potential users and manage expectations, this messaging was carefully crafted with patient input. Second, since most patients do not associate specific safety issues with appropriate remedial or preventative actions, the centerpiece of the application is a table that connects safety issues with related "Questions you should ask" and "Things you can do". Third, patients need understandable explanations of medical terms and concepts as well as explanation of changes in risk; the tool includes plain language "translations" of all medical terms used, links to curated patient education materials, and simplified graphics to visualize changes in risk. Discussion: Our findings may generalize to other efforts to engage patients in their care. Practice value: Designing for patient engagement requires patients' perspective both on their current role and their ideal role; framing for expectations, action-oriented design, and clarity of presented information may address that gap in patient engagement.